Joint-de: sistema de mapeamento objeto-ontologia com suporte a objetos desconectados - Cavalcanti Neto, Olavo de Holanda (2014)
In the last few years, it is increasing the development and use of ontologies in creating more intelligent and effective applications that aim to solve problems commonly found on the Web. This popularity is due to the fact that ontologies attempt to provide semantics to the data consumed by machines, so that they can reason about these data. However, the large adoption of the Semantic Web can be further accelerated by providing sophisticated tools that lower the barrier to the development of applications based on RDF and OWL. Developers of applications with relational databases are already familiar with tools like Hibernate, which provide an object-relational mapping and the management of the objects states. Actually, the main object state that Hibernate provides is the detached. Nevertheless, the great majority of the object-ontology mapping systems (OOMS) only provide persistent objects. The big difference between these two types of objects is that the former one has its life cycle independent of the underlying triple store connection, but the latter one is bounded to the connection. In this context, this paper proposes the creation of an object-ontology mapping systems that supports detached objects, called Joint-DE. With this system, developers of ontology-based applications can: i) use the objects coming from the triple store as objects of the business model; ii) use such objects as data transfer objects ( DTOs) between subsystems and; iii) develop small transactions with detached objects that represent a long transaction unit for the application user. To illustrate the benets of the proposed system, a case study of a real application is presented, outlining the architectural limitations of the application using an existing OOMS in the literature, as well as showing positive results to the use of JOINT-DE. Finally, an experiment was planned and executed aiming to compare the JOINT-DE with another OOMS widely used by the community: Alibaba. The statistical analyzes performed in this experiment showed satisfactory results with regard to JOINT-DE.